2019
DOI: 10.21037/tcr.2019.01.27
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SOX11 and HER2 and their association with recurrent breast cancer

Abstract: Background Recurrent breast cancer occurs as a result of divergent gene expression in response to therapeutic intervention. A recent report showed that SOX11 , an embryogenic mammary transcription factor, is overexpressed in breast cancer. HER2 is also dysregulated in breast cancer stem cells; however, the relative expression of these two genes in recurrent breast cancer has not been investigated. Methods Mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Breast cancer is the most commonly diagnosed cancer (11.6%) and the leading cause of cancer death (6.6%) among females worldwide ( 1 ). Different subtypes of breast cancer have distinct risk profiles and prognosis ( 2 ). Approximately 20% of breast cancer patients are human epidermal growth factor 2 (HER2)-positive, which was known to have a poorer prognosis before the development of targeted therapies ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most commonly diagnosed cancer (11.6%) and the leading cause of cancer death (6.6%) among females worldwide ( 1 ). Different subtypes of breast cancer have distinct risk profiles and prognosis ( 2 ). Approximately 20% of breast cancer patients are human epidermal growth factor 2 (HER2)-positive, which was known to have a poorer prognosis before the development of targeted therapies ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that SOX11 was highly expressed in the central nervous system, gastrointestinal tract, lung, spleen, pancreas, kidney and gonads in normal humans [ 12 , 13 , 14 ]. SOX11 was reported to be highly expressed in breast cancer [ 17 ], mantle cell lymphoma [ 18 ], epithelial ovarian cancer [ 19 ] and hepatocellular carcinoma [ 20 ], while it was expressed at low levels in nasopharyngeal carcinoma [ 21 ], prostate cancer [ 22 ], gastric cancer (GC) [ 23 ] and bladder cancer [ 24 ]. However, we discovered that SOX11 expression was altered in 27 cancer tissues from the TCGA database compared to normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the expression levels of SOX11 vary in different cancer types. For example, a high level of SOX11 mRNA can be detected in many types of tumors, including breast cancer [ 17 ], mantle cell lymphoma [ 18 ], epithelial ovarian cancer [ 19 ] and hepatocellular carcinoma [ 20 ]. In contrast, a low expression of SOX11 was frequently observed in other cancers, such as nasopharyngeal carcinoma (NPC) [ 21 ], prostate cancer [ 22 ], gastric cancer (GC) [ 23 ] and bladder cancer [ 24 ].…”
Section: Introductionmentioning
confidence: 99%